1976
DOI: 10.1111/j.0954-6820.1976.tb06697.x
|View full text |Cite
|
Sign up to set email alerts
|

Thromboembolic Complications, Heparin Treatment and Increase in Coagulation Factors in Cushing's Syndrome

Abstract: Seven of 19 consecutive patientswith Cushing's syndrome demonstrated thromboembolic manifestations before or after adrenaleetomy. These were successfully treated with heparin. The mean values of coagulation factors VIII (AHF) and V as well as prothrombin were increased. There was a positive correlation between the increase in factor VIII content and the severity of disease. The possibility that these changes in blood coagulation activity reflect an increased coagulability state in Cushing's syndrome is discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(21 citation statements)
references
References 24 publications
3
18
0
Order By: Relevance
“…Increased levels of serum factor VIII, von Willebrand factor (vWF), plasminogen, tissue plasminogen activator (t-PA) antigen and PAI-1 activity has been observed in the patients with Cushing's syndrome as compared to healthy controls (11)(12)(13). Conversely, in another study patients with Cushing's syndrome had mean PAI-1, t-PA and vWF-Ag levels insignificantly different from those found in the controls (15).…”
Section: Recent Clinical Studies Have Indicated Various Abnormalitiesmentioning
confidence: 95%
See 2 more Smart Citations
“…Increased levels of serum factor VIII, von Willebrand factor (vWF), plasminogen, tissue plasminogen activator (t-PA) antigen and PAI-1 activity has been observed in the patients with Cushing's syndrome as compared to healthy controls (11)(12)(13). Conversely, in another study patients with Cushing's syndrome had mean PAI-1, t-PA and vWF-Ag levels insignificantly different from those found in the controls (15).…”
Section: Recent Clinical Studies Have Indicated Various Abnormalitiesmentioning
confidence: 95%
“…Increased levels of PAI-I, t-PA, vWF-Ag, II, V, VIII, IX, XIII clotting factors, and depletion of antithrombin-III have been reported (4,(11)(12)(13). In a small series of patients with the active disease Fatti et al…”
Section: Some Studies Focused On Coagulation and Fibrinolysis Parametmentioning
confidence: 96%
See 1 more Smart Citation
“…Several small reports have reported an increased incidence of both venous and arterial thrombotic events in patients with active Cushing's syndrome (61)(62)(63)(64)(65)(66)(67)(68), underlining the existence of a prothrombotic state in this condition. To date, a number of studies have experimentally explored the effects of acute hypercortisolism on the coagulation and fibrinolytic systems (1).…”
Section: Cushing's Syndromementioning
confidence: 99%
“…1). In addition to plasma VWF and factor VIII, some studies have shown higher levels of other coagulation factors such as factors IX, XI, and XII [5,6,7,8,9,10,11,12,13,14,15,16]. …”
Section: Quantitative Alterations: Increased Clotting Factors and Impmentioning
confidence: 99%